Otimização topológica de um disco de freio para um veículo de fórmula SAE - Acorinte, Paulo Eduardo Blanco (Universidade Federal de São Carlos, 2025)
This work aims to apply topology optimization in the design of a brake disc for a Formula SAE vehicle, seeking to reduce its mass without compromising structural integrity and thermal performance. Initially, a vehicle dynamics analysis was conducted during the braking process, considering the conversion of mechanical energy into thermal energy and its impact on the disc structure. The mathematical modeling of thermal behavior was carried out using the lumped capacitance method, allowing the estimation of temperature evolution over time. The adopted methodology involved creating structural models of the brake disc in ANSYS software, where boundary conditions were applied based on the Formula SAE Brake Test. From the analyses performed, it was possible to identify critical stress regions and propose a material redistribution without compromising the component’s strength. The results showed that the optimization led to a mass reduction of up to 21.71% while keeping the maximum stress below the yield strength of the chosen material, AISI 1045 steel. Furthermore, a comparative analysis between the models before and after optimization indicated an improvement in the overall energy efficiency of the vehicle, with a reduction in the mass moment of inertia of the disc, in addition to the mass reduction itself. It is concluded, therefore, that topology optimization is an effective tool for developing lighter and more efficient automotive components.
Topological optimization of a brake disc for a Formula SAE vehicle
Keywords: Otimização topológica; Disco de freio; Fórmula SAE; Topological optimization; Brake disc; Formula SAE; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS